Exclusive Breastfeeding and Normative Belief among Rural Mothers in Ethiopia, 2019: A Cross-Sectional Survey Embedded with Qualitative Design - Wolde Melese Ayele (Obstetrics and Gynecology International)
Background. Exclusive breastfeeding has an irrepressible benefit to a child. However, the practice is still low with salient factors in Ethiopia. Therefore, this study aimed to assess exclusive breastfeeding practice and normative beliefs among mothers who have children less than two years of age in Ethiopia, 2019. Methods. A community-based cross-sectional study was conducted with a sample size of 423 in Ethiopia from March 12 to December 18, 2019. An interviewer-administered questionnaire was used to collect the data. Gender-matched six Focus Group Discussions were conducted. Semistructured guiding questions were used to carry out the discussion. The binary logistic regression model was used to determine the association between dependent and independent variables of the quantitative part. Results. The prevalence of exclusive breastfeeding practice was 77.5% (95% CI: 73.5, 81.5%). Married mothers (AOR = 2.57; 95% CI: 1.68, 5.65), mothers with antenatal care follow-up (AOR = 4.11; 95% CI: 2.66, 11.17), mothers who delivered at a health institution (AOR = 4.07; 95% CI: 2.99, 10.72), and mothers counseled during antenatal care (AOR = 1.96; 95% CI: 1.12, 4.73) had a positive association, whereas mothers who were unable to read and write (AOR = 0.11; 95% CI: 0.06, 0.99) and employed mothers (AOR = 0.22; 95% CI: 0.16, 0.56) were the variables that had a negative association with exclusive breastfeeding practice. Conclusions. Although the prevalence of exclusive breastfeeding was good when compared with other studies, rigorous interventions are needed to achieve the WHO recommendation of all infants should exclusively be breastfed. Marital status, educational status, occupation, antenatal care service, place of birth, and counseling of mothers during ANC were factors associated with the exclusive breastfeeding practice.